Report of the Legal Services of the Parliament of Catalonia on the effects of the Decision of the Central Electoral Board 2/2020, regarding the “subsequent ineligibility” of the deputy Joaquim Torra i Pla (2019.12.19) - Ridao Martín, Joan (Journal of the Basque Parliament, 2020)
Agreement 2/2020 of the Central Electoral Board urged the withdrawal of the parliamentary credential of the deputy Joaquim Torra, sentenced to a special disqualification for a non-final judgment, by resorting to the figure of the “supervene inelegibility” established in the article 6.2.b of the Organic Law of General Electoral Regime. The legal services of the Catalan parliamentary chamber prepared a deeply critical report with said agreement, in which not only the improper use of said figure was reproached, but also its use with the sole purpose of configuring a type of automatic incompatibility, completely subtracted from mandatory control and parliamentary process of the appreciation of incompatibility. In the opinion of the report, of such improper arrogance, the nullity of the provisions of Agreement 2/2020 results, which also seriously violates the rights of political participation of Deputy Torra ex Article 23.2 of the Spanish Constitution, insofar as it interrupts Illegally develop his work as an elected representative. The report also considers the affectation that occurs on the simultaneous condition of President of the Generalitat held by Deputy Torra and concludes that, in the particular conditions of the ordering in Catalonia of said figure, the withdrawal of the status of deputy does not take place, by itself, the effect of automatic termination on the office of the president.
Keywords: parliamentary law; electoral administration; causes for the cessation of deputies; parliamentary incompatibilities; supervene inelegibility; causes for the cessation of the president of the government